Variants Associated with Susceptibility to Pancreatic Cancer and Melanoma Do Not Reciprocally Affect Risk - Wu, Lang (2014)
BACKGROUND: Melanoma cases may exist in pancreatic cancer kindreds, while there is increased risk of pancreatic cancer in familial melanoma. The two cancers may share genetic susceptibility variants in common. METHODS: Three dbGaP-deposited GWAS datasets (MD Anderson melanoma, PanScan 1, and PanScan 2 for pancreatic cancer) were used. Thirty-seven melanoma susceptibility variants in 22 genomic regions from published GWAS, plus melanoma-related genes and pathways were examined for pancreatic cancer risk in the PanScan datasets. Conversely, nine known pancreatic cancer susceptibility variants were examined for melanoma risk in the MD Anderson dataset. RESULTS: In the PanScan data, initial associations were found with melanoma susceptibility variants in NCOA6 (rs4911442) (OR=1.32, 95% CI 1.03–1.70, p=0.03), YWHAZP5 (rs17119461) (OR=2.62, 95% CI 1.08–6.35, p=0.03), and YWHAZP5 (rs17119490) (OR=2.62, 95% CI 1.08–6.34, p=0.03), TYRP1 (p=0.04), and IFNA13 (p=0.04). In the melanoma dataset, two pancreatic cancer susceptibility variants were associated: NR5A2 (rs12029406) (OR=1.39, 95% CI 1.01–1.92, p=0.04) and CLPTM1L-TERT (rs401681) (OR=1.16, 95% CI 1.01–1.34, p=0.04). None of these associations remained significant after correcting for multiple comparisons. CONCLUSION: Reported variants of melanoma genes and pathways do not play a role in pancreatic cancer predisposition. Reciprocally, pancreatic cancer susceptibility variants are not associated with melanoma risk. IMPACT: Known melanoma-related genes and pathways, as well as GWAS-derived susceptibility variants of melanoma and pancreatic cancer, do not explain the shared genetic etiology of these two cancers.